2017
DOI: 10.1177/0003319717715579
|View full text |Cite
|
Sign up to set email alerts
|

High Resting Heart Rate and High BMI Predicted Severe Coronary Atherosclerosis Burden in Patients With Stable Angina Pectoris by SYNTAX Score

Abstract: We investigated the independent and combined association of resting heart rate (RHR expressed as beats/min, bpm) and body mass index (BMI) with SYNTAX score (SS) in patients with stable angina. We divided 312 patients into 4 groups according to RHR quartiles: Q1 (<65 bpm), Q2 (65-69 bpm), Q3 (70-79 bpm), and Q4 (≥80 bpm). The SS (12.0 ± 9.0, 16.0 ± 15.5, 18.0 ± 16.5, and 20.0 ± 27.5; P < .001) was significantly higher for those in Q4 than for those in Q1, Q2, and Q3. Multivariate logistic regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The maximum heart rate increase appears at around BMI 21.13 (male) and 20.16 (female). However, among participants with larger BMIs, decreasing change in heart rate is accompanied by extended time to reach the maximum heart rate, indicating a decreasing rate of heart rate increment, which is not providing evidence for the previous research [1,8]. The HRrecovery reects the eect of PNS reactivation and is usually measured 1 minute after the termination of tness training.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The maximum heart rate increase appears at around BMI 21.13 (male) and 20.16 (female). However, among participants with larger BMIs, decreasing change in heart rate is accompanied by extended time to reach the maximum heart rate, indicating a decreasing rate of heart rate increment, which is not providing evidence for the previous research [1,8]. The HRrecovery reects the eect of PNS reactivation and is usually measured 1 minute after the termination of tness training.…”
Section: Resultsmentioning
confidence: 74%
“…7 Some studies reported a correlation between BMI and resting heart rate, as BMI is a good indicator of obesity. 8,9,10 It will be pretty helpful when considering the Correlation of BMI with HR increment during physical exercises and HRrecovery afterwards. Considering this, a pilot and rst of its kind study was concluded in the IBD nan shi fu zhang, Nanjing Normal University, China.…”
Section: Introductionmentioning
confidence: 99%